Digital Twin Architecture for a Flow Shop Assembly System - Lee, Gihan; Chang, Seunghwan; Park, Sangchul; Yu, Onyu; Yoon, Jungik (Proceedings - Winter Simulation Conference, 2023)
This paper proposes a digital twin architecture for a flow shop assembly line to maximize productivity and reduce quality costs. The proposed digital twin architecture consists of five major modules; Synchronization module to synchronize a real factory and the digital twin, Monitoring module to provide intuitive information visualization, Event calendar initialization module to initialize the factory state at any given time to the starting point of the CPS (Cyber-Physical System) simulation, CPS simulation module to identify potential production losses, and Decision-making module to take proactive actions to avoid anticipated production losses. The proposed digital twin architecture has been implemented for a home appliance factory of LG Electronics Co., Ltd. In South Korea, and shows significant improvements in terms of productivity, quality cost, and energy efficiency.
Keywords: Assembly line; Assembly systems; Cybe-physical systems; Cyber-physical systems; Flow-shops; Information visualization; Production loss; Quality costs; Synchronization modules; System simulations